THE EFFECT OF PROCUREMENT COMPLIANCE BEHAVIOR ON QUALITY OF SERVICE DELIVERY: A CASE STUDY OF THE ELECTRICITY COMPANY OF GHANA (ECG) - Mansaray, Abdul Karim; Lapkoff, Dr. Monica; Little, Anthony (International Journal of Supply Chain Management, 2018)
Purpose: The purpose of this study was to model the effect of procurement compliance behavior on quality of service delivery Methodology: The study adopted an explanatory research design in order to achieve the study objectives. The population for this research was made up of the employees of ECG and the customers of ECG, who were systematically sampled. Data was then analyzed through descriptive statistics using the Statistical Package for Social Science. The study employed descriptive statistics, multivariate data analysis as well as regression models Results: The study found out that compliance levels were just low in the ranks of ECG; about 15.9%. Non-compliance complements this score by recording an alarming 84.1%. This level of compliance is unacceptable by any standard, no matter how it is justified Unique contribution to theory, practice and policy: There is the need to improve compliance levels in the ranks of ECG is very imperative. It would be necessary to strategically work at improving compliance levels through professional procurement training, monitoring of processes for adherence to established policies and standard operating procedures including independent auditing